INCREASING EVIDENCE FOR THE SAFETY OF FOVEA-INVOLVING HALF-DOSE PHOTODYNAMIC THERAPY FOR CHRONIC CENTRAL SEROUS CHORIORETINOPATHY. Issue 3 (2nd March 2023) - Feenstra, Helena M. A.; Diederen, Roselie M. H.; Lamme, Martine J. C. M.; Tsonaka, Roula; Fauser, Sascha; Yzer, Suzanne; van Rijssen, Thomas; Gkika, Theodora; Downes, Susan M.; Schlingemann, Reinier O.; Hoyng, Carel B.; van Dijk, Elon H. C.; et al.
Abstract : Supplemental Digital Content is Available in the Text. None of the chronic central serous chorioretinopathy patients who received a single treatment with fovea-involving half-dose photodynamic therapy in two randomized clinical trials showed signs of developing foveal atrophy after treatment. This adds to the evidence that half-dose photodynamic therapy is a safe long-term treatment for chronic central serous chorioretinopathy patients. Abstract : Purpose: A retrospective study was performed with data from the prospective randomized controlled trials, PLACE and SPECTRA, assessing the risk of foveal atrophy and the likelihood of structural and functional improvement on optical coherence tomography, after foveal half-dose photodynamic therapy in chronic central serous chorioretinopathy. Methods: A total of 57 chronic central serous chorioretinopathy patients received a single half-dose photodynamic therapy with a treatment spot that included the fovea. Optical coherence tomography scans and fundus autofluorescence images were analyzed for structural improvement and possible atrophy development, at baseline and at several visits after treatment. Main outcome measures were integrity of the external limiting membrane and ellipsoid zone on optical coherence tomography and hypoautofluorescence on fundus autofluorescence. Results: The subfoveal external limiting membrane was graded as continuous in 21 of 57 of patients (36.8%) at baseline, and the subfoveal ellipsoid zone was graded as continuous in 5 of 57 patients (8.8%) at first visit, which improved to 50 of 51 (98.0%) and 32 out of 51 (62.7%) at the final visit at 2 years, respectively (both P < 0.001). Hypoautofluorescent changes on fundus autofluorescence were present in 25 of 55 patients (45.5%) at baseline and in 23 of 51 patients (45.1%) at the final visit ( P = 0.480). Conclusion: In patients with chronic central serous chorioretinopathy who received a single, foveal, half-dose photodynamic therapy, a significant improvement in structure and function was seen at the final follow-up. None of the patients developed foveal atrophy.